Plasma catecholamines and renin activity in wrestlers following vigorous swimming - Vigas, M.; Celko, J.; Jurankova, E.; Jezova, D.; Kvetnansky, R. (Physiological Research, 1998)
Cardiovascular and neuroendocrine responses to exercise in a physically fit and an untrained group of young healthy subjects were compared to study the significance of physical fitness for performance in a discipline for which the athletes were not trained. Ten wrestlers of national rank prepared for an international competition (age 18 years) and 9 untrained healthy males (age 21 years). Exercise consisted of 27-min swimming, freestyle, in water of 29 degrees C, with last 3 min increased to maximal effort. The blood pressure, heart rate and sublingual temperature were measured and blood samples were withdrawn before exercise, immediately after and after a 30 min period of rest. Catecholamines were analyzed by radioenzymatic method and plasma renin activity (PRA) using commercial kits. Systolic blood pressure and heart rate after swimming were increased comparably in the two groups, diastolic pressure was unchanged in the controls and decreased in the wrestlers. Plasma cortisol remained unchanged. Plasma glucose tended to increase in the controls and so decrease in wrestlers, with a significant difference between them after swimming (p < 0.05). However, plasma adrenaline was concomitantly increased in both groups (p < 0.01). Noradrenaline and PRA were increased after swimming in both the control and trained group. The increments of noradrenaline and PRA in wrestlers were significantly reduced compared to the control group (p < 0.01, p < 0.05, respectively). Higher physical fitness in athletes significantly reduced plasma noradrenaline and angiotensin responses to maximal exercise demanding special skill in work performance which had not been included in their training program. Training of wrestlers did not cause an exaggerated plasma adrenaline response to exercise.